THE IMPORTANCE OF ENGLISH LANGUAGE TEACHING WITH DEDUCTIVE AND INDUCTIVE APPROACHES (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
This article examines deductive and inductive methods in teaching English, highlighting their benefits and challenges. The deductive method presents rules first, aiding quick grammar learning. The inductive method involves deriving rules from examples, promoting deeper understanding and critical thinking. The article suggests that combining both methods enhances student engagement and learning outcomes, considering context, learner preferences, and goals.